Filsafat Ilmu sebagai Landasan Holistis Pengembangan Ilmu Psikologi - Juneman, Juneman; Pradipto, Yosef Dedy (Humaniora, 2013)
Psychology has long been accepted by many scholars as a science. Nevertheless, intensive readings on philosophy of science and psychology in Indonesia are rarely found. Meanwhile, there are not many professional psychologists nor psychology scientists deliver a course on Philosophy of Science in the faculties and study programs of psychology. The common argument proposed is that both psychologists and lecturers on psychology are not well qualified nor confident enough to teach the Philosophy of Science subject, as if the subject "is only taught" by philosophers or alumni of philosophy department. This phenomenon depicts that there are two worlds: the psychology world and the "other world", philosophy. This straight differentiation is certainly both unnecessary and dangerous as philosophy of science is indeed inherent in any psychological discussions. This article proposed that philosophy of science is a holistic base for the development of psychology and that the relationship between philosophy of science and psychology is close and tight. Psychologists are expected to take more part in inquiring assumptions and values in psychology and thus the simplification of psychology as a technical psychodiagnostic could be avoided.